The effects of Monetary Policy shocks across the Greek Regions - Ageliki Anagnostou; Stephanos Papadamou (European Regional Science Association (ERSA), 2012)
In this paper, we examine the impact of monetary policy shocks to the real economy by investigating the effects on different regions. Annual data for GDP, employment and investment from 12 regions in Greece are used for the period 1980 to 2009. By using an unrestricted VAR model and the impulse response analysis our results show that an interest rate shock affects the economic activity across regions differently. Furthermore in our investigation, we use a dynamic PANEL VAR model so as to investigate the dynamic variation of the impact of interest rates controlling also for time and cross regions fixed effects associated with specific time invariant regions' characteristics as well as with time variant characteristics attributed to the integration process of these regions. Therefore, these findings are very important to policy makers.
Keywords: 330